1474. Impact of 13-valent Pneumococcal Conjugate Vaccine (PCV13) on Non-bacteremic Pneumococcal Pneumonia (NBPP) among Adults in the United States, 2013-2017. (31st December 2020) - Gierke, Ryan; Matanock, Almea; Shang, Nong; Farley, Monica M; Schaffner, William; Thomas, Ann; Reingold, Art; Harrison, Lee; Schleiss, Katherine; Burzlaff, Kari; Petit, Susan; Alden, Nisha B; et al.
Abstract: Background: PCV13 was recommended for U.S. children in 2010 and for adults ≥ 65 years in 2014. Vaccine coverage among adults ≥ 65 years was 43% in 2017. We evaluated PCV13 impact on NBPP among adults. Methods: NBPP cases (clinically or radiographically confirmed pneumonia and a positive pneumococcal urine antigen test (PUAT) in a hospitalized adult aged ≥ 18 years) were identified at select hospitals in 10 sites within CDC's Active Bacterial Core surveillance during 2013-2017. NBPP rates (per 100, 000) were estimated using U.S. Census Bureau population denominators and adjusted for the proportion of pneumonia patients tested by PUAT and the number of pneumonia admissions in the catchment area. Results: Between 2013 and 2017, 4, 430 NBPP cases were identified. Adults aged ≥ 65 years accounted for 49% of cases. Case fatality rate was 6%. From 2013 to 2014, rates of NBPP declined from 153 to 90 (41% reduction, 95%CI 28%, 51%) in ≥ 65 year-olds; 60 to 40 (34% reduction, 95%CI 22%, 45%) in 50-64 year-olds; and 15 to 10 (36% reduction, 95%CI 25%, 47%) in 18-49 year-olds. From 2014 to 2017, rates of NBPP increased in all ages, but remained below 2013 rates (Figure). Figure. Estimated Annual Non-Bacteremic Pneumococcal Pneumonia Incidence by Age Group, 2013–2017 Conclusion: Reductions in NBPP among adults were primarily due to indirect effects of PCV13 use in children, with no additional declines following PCV13 introduction for adults aged ≥ 65 years. Disclosures: Lee Harrison, MD, GSK (Consultant)Merck (Consultant)Pfizer (Consultant)Sanofi Pasteur (Consultant) Nisha B. Alden, MPH, CDC (Grant/Research Support)